Application of the Hot Seat Method in SKI Learning by MAN 2 Soppeng - Awaluddin, A. Fajar; Usman, Farhan; Zubaedy, M.; Riska, Riska; Saipul, Muh. (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to analyze the application of the hot seat method in learning Islamic Cultural History (SKI) at MAN 2 Soppeng and its contribution to the level of mastery of students' material. The research background departs from the need for learning innovations that are able to increase active participation, conceptual understanding, critical thinking skills, and students' courage in expressing opinions. This study uses a qualitative descriptive approach. Data collection techniques are carried out through observation, in-depth interviews, and documentation. Data are analyzed by data reduction, data presentation, and conclusion drawing techniques. The results of the study show that the Hot Chair method is applied through three stages, namely preparation, implementation, and evaluation. In the implementation stage, students take turns sitting in the "hot seat" to answer questions from teachers and classmates, while teachers act as facilitators and discussion directors. The obstacles faced include embarrassment and lack of confidence in some students at the beginning of the application, limited learning time, and significant differences in abilities between students. The solutions carried out include providing motivation, proportional timing, and class management so that all students get the same opportunity to participate. The contribution of the Hot Chair method to SKI learning can be seen from the increase in the accuracy of answers, the ability to explain material in their own language, analytical skills, and the courage of students to express their opinions. This method also encourages active participation, boosts confidence, and creates an interactive and fun learning atmosphere. These findings indicate that the Hot Chair method is effective in improving mastery of SKI material and is suitable as an alternative to active learning strategies in madrasah. Keywords: